Assisting MSME Traders in Pandan Lagan Village in Complying with Halal Products - Andini, Sukma Tri; Kuswanto; Safitri, Ria Astuti (Future Tecno-Science Publisher, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the local economy, including in Pandan Lagan Village, Geragai District, Tanjung Jabung Timur Regency. However, many MSME actors still lack awareness regarding compliance with halal product standards as part of their moral and legal responsibilities. This community service project aims to enhance MSME actors’ understanding, awareness, and capability in the halal certification process and the application of halal principles in production and distribution. The program includes halal regulation socialization, technical training on halal certification documentation, and consultative assistance for registration with BPJPH. The results show an 85% increase in MSME knowledge of halal principles and growing commitment to registering their products for halal certification. The program also established a village halal companion group to sustain the halal economy movement locally.